A morte iminente e a ressignificação da vida na velhice: uma análise do filme Antes de Partir - Teodoro, Giovana Gianotti (Universidade Federal de São Carlos, 2022)
The discovery of a life-threatening disease has a significant impact on the elderly, given the complexity of the process of coping and resilience. In the course of the pandemic scenario, illness and death became the main agenda of science and the media, highlighting adjacent themes, such as mourning, spirituality and meaning of life, regarding the following question: imminent death is a factor of resignification of life in old age? Therefore, the objective of this study is to reflect on the theme of imminent death, which is one of the determining factors for the re-signification of life in old age, through the analysis of the film The Bucket List (2007). Bibliographic research was carried out using the Google Scholar, LILACS and Scielo platforms, on the themes of death, finitude, mourning, meaning of life, aging and cinema. It was evidenced that the imminent death and the questions that permeate it can bring to the individual a new meaning for his life.
Imminent death and the resignification of life in old age: an analysis of the film The Bucket List
Keywords: Velhice; Cinema; Ressignificação da vida; Old age; Resignification of life; CIENCIAS DA SAUDE